Corn Transformation Machine as Media Increases Threshing Productivity of Corn Village Prupuh, Panceng Sub - District, Gresik Regency - Syaifudin Syaifudin; Muhammad Wahyu Firmansyah; Muhammad Zainuri; Siska Anggraeni; Muhammad Wahyu Romadhon; Fery , Lasiyano A; Dimas Eko C; Rosikhul Islah I; Baso Mukramin (Kontribusia : Research Dissemination for Community Development, 2019)
Prupuh village is a village in the district Panceng by having a hamlet that Hamlet Prohibition. 2000more residents in the village Prupuh with 575 heads of household, and 400 homes were built. In generallivelihoods of the majority of the villagers are farmers Prupuh. In the rainy season corn is one of the cropsgrown by the residents both in the fields and in the yard. Corn Transformation Machine addressed to thevillagers of Prupuh that planting corn with manual harvesting. People have become less productive becauseof the time needed to separate the corn from bongkolnya very long. From the experimental results usingCorn Transformation Machine tool time needed to separate the corn seed from bongkolnya ie 30 secondsper 1 piece of corn, while if using a hand (manual) takes 5 minutes per 1 piece of corn. The tool can savetime for 4.5 minutes and simultaneously increase productivity the amount of corn kernels are separatedfrom bongkol.